2002
DOI: 10.1159/000058405
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine Inhibits <i>D-</i>Amino Acid Oxidase

Abstract: Inhibition of D-amino acid oxidase (DAO) activity by various uremic retention products and guanidino compounds was investigated. Creatinine (CTN) was found to inhibit DAO at a similar concentration in the sera of uremic patients. The inhibition was competitive and the Ki value was 2.7 mM. Moreover, CTN was shown to interact with flavin adenine dinucleotide (FAD), a coenzyme of DAO. The UV spectral change of FAD bound to DAO was observed in the visible region by addition of CTN. These findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Such restoration in GSSG-Rd after PS dialysis may reflect a greater capacity to eliminate flavin nucleotides from uremic plasma than CU dialyzer. It has been shown that FAD can bind tightly to guanidine compounds and creatinine (29). Removal of these substances is better with PS than CU and could contribute to the observed reduction in GSSG-Rd after PS dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Such restoration in GSSG-Rd after PS dialysis may reflect a greater capacity to eliminate flavin nucleotides from uremic plasma than CU dialyzer. It has been shown that FAD can bind tightly to guanidine compounds and creatinine (29). Removal of these substances is better with PS than CU and could contribute to the observed reduction in GSSG-Rd after PS dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the sources of dietary D-amino acids is microorganism, so they serve as an indicator for the presence of bacterial contaminants in food or a monitor for a fermentation process (Gandolfi et al, 1992;Inaba et al, 2003). D-Amino acids are drawing much attention especially for clinical diagnosis because it has been suggested that the measurement of plasma D-amino acid level can be employed for the diagnosis of renal failure disease (Nagata et al, 1987;Nohara et al, 2002). In addition, D-amino acids are proposed to be indicators of aging because age-related accumulation was observed in lens protein and brain tissue (Man et al, 1987;Poinar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%